Association of Vitiligo with Thyroid Dysfunction and Thyroid Autoimmunity: A Case-Control Study - Habib, Aamir; Shaheen, Sohail; Arif, Nida (Pakistan Armed Forces Medical Journal, 2026)
Objective: To assess the association of thyroid dysfunction and thyroid autoimmunity with vitiligo. Study design: A case-control study. Place and Duration of Study: Outpatient of Dermatology Department of a tertiary referral hospital Bahawalpur, Pakistan, from Jan to Dec 2023. Methodology: A total of 207 vitiligo patients (Group-A) and 207 controls (Group-B) of similar age and gender were enrolled. Pregnant females, patients already getting any form of treatment for vitiligo and those with any diagnosed autoimmune disease were excluded. The onset age, sites involved by the disease and associated diseases were noted. Thyroid profile and anti- thyroid peroxidase antibodies were tested in all patients and controls. A p-value less than 0.05 was considered statistically significant. Results: Out of 207 patients, 117(56.521%) were male patients and 90(43.478%) were female. Mean onset age was 27.320±10.467 years and mean disease duration was 4.700+5.996 years. Generalized vitiligo was the most common type found in 120 (57.971%) patients. Sixty-eight (32.850%) patients had a positive family history and associated diseases were found in 25 (12.077%) patients. Thyroid dysfunction manifested by deranged Thyroid Hormone Levels was found in 20 (9.662 %) patients and 4 (1.932%) controls (p=0.001). Level of Anti-TPO Antibodies was raised in 17 (8.212 %) patients and in 3 (1.449%) controls (p=0.001). Conclusion: Vitiligo is significantly associated with thyroid dysfunction and thyroid autoimmunity.